1983
DOI: 10.1103/physrevlett.51.257
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Test of Higher-Order QED and a Search for Excited Muon States

Abstract: The reactions e *e ~-*JU "V "y> and e*e --*/I + JLI "y have been studied at \ r s = 29 GeV with the MAC detector at the SLAC storage ring PEP. The measured cross sections, charge asymmetry, and invariant-mass distributions are in good agreement with the predictions of QED theory. Limits are derived for the production of excited muon states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Further studies will be needed before we have any practical method for the measurement of quark spin polarization. Some rather nice y interference experiments have been done recently by Ford et al (1983) and Bartel et al (1984), which also demonstrate clearly how quarks behave like charged leptons, underneath their fragmentation disguise. Here, the lepton reaction is similar to the pair-production process considered above, but with the addition of an extra real photon which is detected by the apparatus, e+e_-^p+p_y, e+e~^T +T-y.…”
Section: J Ets: the Materialization Of Quarks And Gluonsmentioning
confidence: 80%
“…Further studies will be needed before we have any practical method for the measurement of quark spin polarization. Some rather nice y interference experiments have been done recently by Ford et al (1983) and Bartel et al (1984), which also demonstrate clearly how quarks behave like charged leptons, underneath their fragmentation disguise. Here, the lepton reaction is similar to the pair-production process considered above, but with the addition of an extra real photon which is detected by the apparatus, e+e_-^p+p_y, e+e~^T +T-y.…”
Section: J Ets: the Materialization Of Quarks And Gluonsmentioning
confidence: 80%
“…TeV including contact interactions in the µ ⋆ production and decay mechanism, the ATLAS collaboration sets the mass limits as m µ * > 3000 GeV [40]. Other studies on excited muon searches can be found in [41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%